TEACHING COMPLEX ENGLISH GRAMMAR BY USING KAHOOT APPS - Lailatul Masruroh (English Language Teaching Department (Prodi Pendidikan Bahasa Inggris), 2019)
Teaching English as a second or foreign language wants variation and creative thinking of the teacher so as to create the category additional joyful and relaxed that creates students additional eager and fascinated by connection the category. Kahoot that's designed as a mixture of ICT use in education of grammatical and the right sentences and tences. This study was conceived in qualitative study, data on the use of Kahoot online software in English classrooms were collected from several related literature. This present study took some previous study which demonstrated the effectiveness of students using video as a learning medium, particularly EFL classes. Furthermore, the teacher must also be able to deliver good material using Kahoot online application as a model. In addition, teachers must have a step-by-step plan of what the teacher must do during teaching and learning before using this online application as a teaching medium. This study has been assumed by many academics around the world that teaching English using media such as kahoot. This study was done in the 3th semester of students in English Department of Universitas Qomaruddin that the students are consist of 31 students.